Operation Evaluation of Phased Antenna Arrays in Case of Phase Shifter Malfunction - M. R. Bibarsov; A. F. Kryachko; A. V. Pshenichnikov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Stable operation of multi-element antenna systems, in particular waveguide-slotted phased antenna arrays (WSPAA), ensures the required noise immunity and electromagnetic compatibility of radio-electronic equipment for various purposes. However, such performance indicators are subject to deterioration due to the random nature of changes in the phases of antenna elements (AE) under the action of malfunction of phase shifters (PS). Therefore, operation evaluation of WSPAAs in the event of PS failure with any outcome is an urgent research task. The paper reviews algorithms for modeling the impact of PS failures on WSPAAs and evaluates the operation of such antenna systems under these impacts.Aim. Development of an algorithm for assessing the impact of a complete PS shutdown on WSPAA characteristics, as well as operation evaluation of WSPAAs in the event of PS malfunction with different outcomes.Materials and methods. Statistical modeling methods were used to study the impact of PS failures on WSPAA characteristics. Calculations were carried out using in the Mathcad 15 software environment.Results. The conducted simulation revealed three types of faults, for which the following PS parameters were set: the phase took a value equal to 0, instead of the required one; the phase took a random value with a discrete value of 22.5°, instead of the required one; complete switching off of the PS. When studying up to 35 faulty PS of an AE from 50 elements, the following characteristics were changed: standard deviation – from 0.056 to 0.18; relative values: radiation pattern width – from 8 to 32 %; level of side lobes – from 13 to 78 %; radiation power – from 0.9 to 0.31. A range of WSPAA states was formed upon the occurrence of PS failures: "Normal operation" – up to 7 faulty PS; "Deterioration of parameters" – from 7 to 12 faulty PS; "Failure" – more than 12 faulty PS.Conclusion. The results obtained can be used when designing radio-electronic systems with antenna arrays. Future research should be aimed at developing a methodology for operational monitoring of the state of antenna systems, as well as studying the compensation of characteristic distortions in case of various malfunctions.